Islamic mutual funds: risk and return management - Adi Gunanto; Lubna M. Omar Hamzalouh; Sunarmi Sunarmi; Mohammad Ridwan (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This research aims to provide a deeper understanding of the risks associated with investing in sharia fixed income mutual funds and how these risks can affect investment returns.Method - This research adopts a quantitative descriptive research approach that focuses on numerical data. The operational definition of mutual fund risk in this study refers to the concept of risk defined as the variability of returns from the type of securities that will form the portfolio. The securities that are the focus of this research are sharia fixed income mutual funds.Result - The performance of sharia fixed income mutual funds from 2021 to 2022 shows positive and significant developments.Implication - The findings of this research have significant implications for financial policymakers and investors. Furthermore, this research emphasizes the importance of ethical investment choices and compliance with sharia principles, providing investors with financial security and ethical satisfaction.Originality - This research contributes to the field of research by providing a comprehensive analysis of the risk and return characteristics of sharia fixed income mutual funds. Additionally, this research offers a more holistic view of investment performance.